Przekłady książkowe bułgarsko‑polskie i polsko‑bułgarskie w latach 2007—2013 - Gołek‑Sepetliewa, Dorota (Przekłady Literatur Słowiańskich, 2014)
The translations of books from Bulgarian into Polish and from Polish into Bulgarian in 2007—2013 The subject of discussion in this article is translation of Bulgarian books in Poland and Polish books in Bulgaria in the period 2007—2013. In recent years relatively a large number of translations of Bulgarian literature are published in Poland. Collection includes modern novels, short story volumes and anthologies, poetry books. Despite the unfavorable situation, which expressed in the general economic and cultural situation, pro‑Western orientation, limiting the presence of “small” literatures, Bulgarian literature each year attend the Polish publishing market. The successful reception of Polish literature in Bulgaria in the last seven years due to: high quality translations, adequate reflection in the field of literary criticism and literary studies, the financial support of the Polish Institute in Sofia. The result of favorable circumstances have been a large number of translations, which consist: the literary classics and selection of contemporary and recent Polish literature. Keywords: Polish literature, Bulgarian literature, translations